Analysis of the Needs of Interactive Media "CASINO" Based on Think Pair Share for Indonesian Language Learning in Elementary Schools - Nadia Shofyana; Minkha Lailatus Sa'diyah; Raida Fitri Sabrina; Rani Setiawaty (Alifbata : Jurnal Pendidikan Dasar, 2026)
This study aims to analyze the need for interactive media "CASINO" based on Think Pair Share in Indonesian language learning at SD IT Al-Akhyar, especially on synonym material. Data were collected through interviews with fifth grade teachers and questionnaires filled out by 24 students. The results of the study indicate that there is no learning media used, teachers only use conventional teaching materials in the form of worksheets and textbooks so that learning is less interesting. As well as the lack of student understanding in Indonesian language learning, especially on synonym material. Strengthened by the questionnaire data where 41.7% of students do not like Indonesian language learning, because the method is monotonous and too much narrative text. From the material aspect, 87.5% of students understand the concept of antonyms, but only 58.3% understand the concept of synonyms. Teachers stated that they had never used interactive media (such as Interactive PPT) and considered that the TPS model and visual media were very necessary to create more collaborative, effective, and efficient learning in time management. In conclusion, the development of the interactive "CASINO" media based on Think Pair Share is highly relevant and necessary to increase students' interest and understanding of vocabulary concepts at the elementary school level. Keywords: needs analysis, Indonesian, interactive media, casino, think pair share.